Frequency of light fluctuations affects tomato morphology and physiology only at extreme amplitudes - Dieleman, J. Anja; van Steekelenburg, Guido; Weerheim, Kees; Kaiser, Elias; Meinen, Esther; van Hoogdalem, Mark (Frontiers in Plant Science, 2025)
IntroductionElectricity prices can fluctuate considerably during the day due to the dependency of solar and wind energy and varying demands. Fluctuating lighting regimes might thus be economically attractive. However, only limited knowledge is available on how plants grow under fluctuating light conditions. The aims of this study were (1) to determine effects of fluctuating light intensities on plant biomass, morphology and physiology and (2) to determine whether frequency or amplitude of the fluctuations is the main determining factor of such effects.MethodsYoung tomato plants were grown under fluctuating light conditions in a range of amplitudes (200/0, 175/25, 125/75 and 100/100 µmol m-2 s-1) and frequencies (several hours, 30 minutes, minutes).ResultsPlants grown under extreme light fluctuations of 0/200 µmol m-2 s-1 had reduced shoot biomass, stem length, chlorophyll content and light absorption, compared to plants grown under constant light intensity. The higher the frequency of these light fluctuations, the more severe the effects. Plants responded most extremely when light fluctuated every minute between 0 and 200 µmol m-2 s-1, having the lowest shoot dry weight, chlorophyll content, leaf area and light absorption. When light fluctuations were applied every minute between 175/25 and 125/75 µmol m-2 s-1, shoot biomass and morphology were not significantly affected. Net photosynthesis rate of plants grown under 30 min light fluctuations between 200 and 0 µmol m-2 s-1 were reduced compared to constant light and light fluctuations with a smaller amplitude. Linear electron transport rates were significantly reduced for all 200/0 and 175/25 treatments compared to constant light.DiscussionThese results indicate that the frequency of light fluctuations determines plant biomass, morphology and physiology only at extreme amplitudes of light fluctuations. However, when a minimum light level is maintained, the crop can integrate these light fluctuations, maintaining crop growth and development.